2014
DOI: 10.3390/ijms151018819
|View full text |Cite
|
Sign up to set email alerts
|

Metaphylogenomic and Potential Functionality of the Limpet Patella pellucida’s Gastrointestinal Tract Microbiome

Abstract: This study investigated the microbial diversity associated with the digestive tract of the seaweed grazing marine limpet Patella pellucida. Using a modified indirect DNA extraction protocol and performing metagenomic profiling based on specific prokaryotic marker genes, the abundance of bacterial groups was identified from the analyzed metagenome. The members of three significantly abundant phyla of Proteobacteria, Firmicutes and Bacteroidetes were characterized through the literature and their predicted funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 102 publications
0
17
0
2
Order By: Relevance
“…Proteobacteria, for example, is the most abundant phylum present in each gastropod species, as well as in the environmental controls. This is consistent with previous studies that have shown members of this phylum to dominate host‐associated microbiota in marine animals including limpets, corals, copepods and fish (Bayer et al ., ; Dudek et al ., ; Givens et al ., ; Dorosz et al ., ). However, preferential enrichment of different genera, such as Mycoplasma in C. funebralis and Psychrilyobacter in L. gigantea, contributes to significant differences among microbiomes of our four gastropod hosts.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Proteobacteria, for example, is the most abundant phylum present in each gastropod species, as well as in the environmental controls. This is consistent with previous studies that have shown members of this phylum to dominate host‐associated microbiota in marine animals including limpets, corals, copepods and fish (Bayer et al ., ; Dudek et al ., ; Givens et al ., ; Dorosz et al ., ). However, preferential enrichment of different genera, such as Mycoplasma in C. funebralis and Psychrilyobacter in L. gigantea, contributes to significant differences among microbiomes of our four gastropod hosts.…”
Section: Discussionmentioning
confidence: 98%
“…Marine molluscs are one of the most diverse and ecologically important groups of marine invertebrates, with many species providing a variety of ecosystem services including supporting commercial and artisanal fisheries. Information about the diversity and compositions of microbes associated with molluscan hosts still remains scarce, although microbiomes of some bivalve (Prieur et al, 1990;Betcher et al, 2012;King et al, 2012;Lokmer et al, 2016;Pierce et al, 2016;Arfken et al, 2017) and gastropod (Dudek et al, 2014;Zbinden et al, 2014;Aronson et al, 2017;Cicala et al, 2018) species have been quantified. Moreover, existing analyses of marine gastropod microbiomes have primarily focused on the digestive tract, with only one study including gillspecific microbiome data (Zbinden et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, anaerobic bacteria from the classes Fusobacteriia and Mollicutes are only rarely found in coastal waters or associated with macroalgae [ 39 41 ]. However, these bacterial groups seem rather typical of digestive organs of marine holobionts as they are found in the sea squirt Ciona intestinalis , the limpet Patella pellucida , and marine carnivores [ 21 , 42 , 43 ]. Members of Vibrio are well known as pathogen of animals, and it is the most common bacterial genus in guts of marine animals such as the intestinal mucosa of marine fishes [ 35 , 44 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most marine herbivores are generalists, meaning they are able to feed on the three macroalgal lineages, but only few studies have been performed on digestive microbiota in marine herbivores. Bacteria have been shown to help degrade macroalgal polysaccharides in the sea hare Aplysia spp., the snail Tegula funebralis , the limpet Patella pellucida , and the iguana Amblyrhynchus cristatus [ 21 24 ], but these studies considered neither different diet types nor seasonality. The abalone, a gastropod of high economic interest especially in China, Korea, South Africa, and Chile [ 25 , 26 ], is also a generalist herbivore [ 27 ], but its digestive enzymes are not sufficient for macroalgal polysaccharide degradation [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another metagenomic study of the 16S rRNA gene of a bivalve mollusc (internal body parts without the shell) resulted in the discovery of 3553 OTUs from 44 phyla, in which Proteobacteria was found to be the most abundant phylum [ 52 ]. The metagenome of the digestive tract of a marine limpet also revealed diverse microbial communities with the most dominant phylum being Proteobacteria [ 53 ]. Indeed, Proteobacteria accounts for more than 40% of all known prokaryotic genera [ 54 ] and is the dominant bacterial phyla reported from other marine invertebrate taxa, including the sponge Halichondria sp.…”
Section: Discussionmentioning
confidence: 99%